Engineered Nanostructured Nitrogen-Doped Carbon Network (NDC) Electrodes with Unprecedented Cycling Stability for Water Capacitive Deionization in Harsh Conditions - Anwar, Soha Essam (AUC Knowledge Fountain, 2021)
Capacitive deionization (CDI) is a feasible low-cost desalination technique for low-to-medium (brackish) salinity water. However, cycling stability and regeneration of the CDI electrodes are the bottlenecks hindering the practical application of the technology on large scale. Oxidation of the electrodes during the sequential adsorption-desorption processes is one of the most challenging problems hindering their long-term cycling performance. Herein, we demonstrated the ability to design and fabricate exceptionally stable CDI electrodes via a one-pot pyrolysis protocol. The optimized pyrolysis of nitrogen-carbon precursors at different temperatures enabled the fabrication of carbon materials with a controlled amount nitrogen dopant (NDCs) with exceptional cycling stability. The NDCs showed high specific capacitance and dual meso/microporous structures with high salt adsorption capacity (SAC), reaching 26.5 mg.g-1 in a single-pass desalination mode. Moreover, the electrodes exhibited exceptional desalination stability performance over 150 successive charging/discharging cycles in aerated and deaerated solutions with 500 mg L-1 feeds under harsh 1.4 V as the charging voltage. The potential of zero charge (PZC) was determined for the tested NDC electrodes to elucidate their oxidation resistance (EOR). The electrodes exhibited a minimal shift in potential after the entire desalination stability tests, revealing minor electrode oxidation. The performance of our NDC-electrodes was compared against that of the commercially available activated carbon (AC) under the same experimental conditions, with the latter showing a server decrease in the SAC retention within the first few cycles.